Observation of Van Hove Singularities and Temperature Dependence of Electrical Characteristics in Suspended Carbon Nanotube Schottky Barrier Transistors - Zhang, Jian; Liu, Siyu; Nshimiyimana, Jean Pierre; Deng, Ya; Hu, Xiao; Chi, Xiannian; Wu, Pei; Liu, Jia; Chu, Weiguo; Sun, Lianfeng (Nano-Micro Letters, 2017)
A Van Hove singularity (VHS) is a singularity in the phonon or electronic density of states of a crystalline solid. When the Fermi energy is close to the VHS, instabilities will occur, which can give rise to new phases of matter with desirable properties. However, the position of the VHS in the band structure cannot be changed in most materials. In this work, we demonstrate that the carrier densities required to approach the VHS are reached by gating in a suspended carbon nanotube Schottky barrier transistor. Critical saddle points were observed in regions of both positive and negative gate voltage, and the conductance flattened out when the gate voltage exceeded the critical value. These novel physical phenomena were evident when the temperature is below 100 K. Further, the temperature dependence of the electrical characteristics was also investigated in this type of Schottky barrier transistor. Highlights: 1 A clear signature of VHSs in the conductance versus gate voltage was observed in Schottky barrier transistors with an individual suspended single-walled carbon nanotube (SWNT). 2 Critical saddle points appear in regions of both positive and negative gate voltage, and the conductance flattens out when the gate voltage exceeds the critical value.